Strategi Pengembangan Usahatani Terung (Solanum Melongena L) di Kebun Pratek Pertanian Universitas Nusa Nipa Indonesia - Andrianus Poto; Yoseph Yakop Da Rato (Jurnal Ilmiah Wahana Pendidikan, 2022)
Eggplant (Solanum melongena L) is one of the sources of food that is well known by all levels of society. Eggplant is one of the most popular menus in various circles. Besides its delicious taste, eggplant can also be processed into various dishes. internal and external factors in the development of eggplant farming and the strategies used in developing eggplant farming in UNIPA gardens. SWOT analysis is used to answer research problems. Determination of 15 respondents using purposive sampling method. Research results: In the strategy of developing eggplant farming in the Practical Garden of the Faculty of Agriculture, UNIPA uses strengths, weaknesses, opportunities and challenges. The right strategy for developing eggplant in the agricultural practice garden is in quadrant 1 or an aggressive strategy, namely using strength to take advantage of existing opportunities, including: 1). take advantage of awareness of a healthy lifestyle by continuing to use organic fertilizers and maintaining product prices. 2). Increase the utilization of input materials and take advantage of the prospect of organic eggplant to increase customers while maintaining quality